Opportunities for Microalgae-Bacteria Consortium Application to the Treatment of Effluents Generated in Fiber-Waste-Based Recycling Processes - Sátiro, Josivaldo; Leitão, Sanderson; Gomes, Arlindo; Simões, Rogério; Albuquerque, António (KnE Materials Science, 2022)
Technologies based on microalgae-bacteria seem to be sustainable options for wastewater treatment and reuse, with lower costs than conventional biological treatment technologies. Furthermore, they can generate added-value products produced from algae biomass. Among other advantages, the consortium bacteriaalgae produce photosynthetic oxygen through the microalgae, which can be used by aerobic bacteria for oxidizing organic matter and nitrogen, thus reducing the need for introducing artificial oxygen. In this review paper, the main systems that use microalgaebacteria consortium are discussed. Microalgae-bacteria present advantages in the removal of organics, nitrogen and phosphorus, when compared with conventional biological treatment systems (e.g., activated sludge, percolating filters and ponds), and are able to produce final effluents for reuse (e.g., in agricultural irrigation, industry or aquifer recharge) and excess of microalgae that can be converted to added-value products such as biogas and biofuels. Attention is given to the innovative aspects of applying photobioreators to the treatment and reuse of pulp and paper effluents and fiber-waste-based recycling wastewaters, which seems to open a new opportunity for the pulp, paper and recycling paper industries. Keywords: fiber-waste-based industry, microalgae-bacteria consortium, removal of nutrients, wastewater treatment